Different Transcriptomic Response to T. cruzi Infection in hiPSC-Derived Cardiomyocytes From Chagas Disease Patients With and Without Chronic Cardiomyopathy - Oliveira, Theo G. M.; Venturini, Gabriela; Alvim, Juliana M.; Feijó, Larissa L.; Dinardo, Carla L.; Sabino, Ester C.; Seidman, Jonathan G.; Seidman, Christine E.; Krieger, Jose E.; Pereira, Alexandre C. (Frontiers in Cellular and Infection Microbiology, 2022)
Chagas disease is a tropical zoonosis caused by Trypanosoma cruzi. After infection, the host present an acute phase, usually asymptomatic, in which an extensive parasite proliferation and intense innate immune activity occurs, followed by a chronic phase, characterized by low parasitemia and development of specific immunity. Most individuals in the chronic phase remain without symptoms or organ damage, a state called indeterminate (IND) form. However, 20 to 40% of individuals develop cardiac or gastrointestinal complications at any time in life. Cardiomyocytes have an important role in the development of Chronic Chagas Cardiomyopathy (CCC) due to transcriptional and metabolic alterations that are crucial for the parasite survival and replication. However, it still not clear why some infected individuals progress to a cardiomyopathy phase, while others remain asymptomatic. In this work, we used hiPSCs-derived cardiomyocytes (hiPSC-CM) to investigate patterns of infection, proliferation and transcriptional response in IND and CCC patients. Our data show that T. cruzi infection and proliferation efficiency do not differ significantly in PBMCs and hiPSC-CM from both groups. However, RNA-seq analysis in hiPSC-CM infected for 24 hours showed a significantly different transcriptional response to the parasite in cells from IND or CCC patients. Cardiomyocytes from IND showed significant differences in the expression of genes related to antigen processing and presentation, as well as, immune co-stimulatory molecules. Furthermore, the downregulation of collagen production genes and extracellular matrix components was significantly different in these cells. Cardiomyocytes from CCC, in turn, showed increased expression of mTORC1 pathway and unfolded protein response genes, both associated to increased intracellular ROS production.